Ensuring quality in legal translation by 3 parties – governments, courts and translators - Michal Hara (JoSTrans: The Journal of Specialised Translation)
Directive 2010/64/EU of the European Parliament and of the Council of 20 October 2010 on the right to interpretation and translation in criminal proceedings stipulates that EU Member States should introduce safeguards ensuring that translation provided in the course of criminal proceedings is of a sufficiently high quality. This can be achieved by various means by governments, courts and translators: through enacting a legal framework regulating the position, rights and obligations of translators by governments, through appropriate practical arrangements introduced and followed by courts and other judicial and law enforcement authorities and finally by translators themselves through specialisation and targeted improvement of qualifications. Each of the aforementioned groups has different tools and opportunities at their disposal. It seems however clear that an effective system of quality assurance requires the cooperation of all three of them so that the measures enacted complement and support each other, rather than operate in a legal void.